Perceptions of Safety and Stress Among Health Professionals: The Role of Care Unit Identification as a Protective Factor During the COVID-19 Pandemic - Panari, Chiara; Caricati, Luca; Gallo, Gaetano; Bonetti, Chiara; Bonini, Alice; Monacelli, Nadia; Sollami, Alfonso (Frontiers in Psychology, 2022)
The present study aimed to investigate the role of motivational process and coping resources in health professionals during the COVID-19 emergency examining the role of Care Unit Identification and safety climate perception as resources that can help nurses to cope with stressors. A cross-sectional research design was used and 218 nurses completed a self-report questionnaire measuring: Perception of safety, Care Unit identification, Work Engagement, Psychological Distress and Burnout. Results revealed that Work Engagement was significantly related with Burnout (b = -0.209, 95%CI [-0.309; -0.109]) and Distress (b = -0.355, 95%CI[-0.529; -0.18]) especially when the Care Unit identification is high (b = -0.303, 95%CI [-0.448; -0.157] and b = -0.523, 95%CI [-0.772; -0.275] respectively). The safety perception was positively related to Work Engagement (b = 0.315, 95%CI [0.198; 0.433]) and had an indirect effect on psychological Distress (b = -0.112, 95%CI [-0.181; -0.042]) and Burnout (b = -0.066, 95%CI [-0.105; -0.027]). High levels of both Care Unit identification and perception of safety, along with personal work engagement, appear to protect nurses from burnout and psychological distress. Findings suggest that the effort to improve teamwork identification and ensures an adequate degree of perceived safety for healthcare professionals need to be maintained and reinforced as they positively impact nurses’ well-being.